Konsep “Nyari” dalam Ranah Estetika Pertunjukan Wayang Golek - Cahya Cahya; Timbul Haryono; Soetarno Soetarno (LP2M ISBI Bandung, 2012)
ABSTRACTThis paper is a part (portion) of one topic of dissertation research by the author as a preparation for the final exams of doctoral program. The focus of the study in this paper is directed to study aspects of the aesthetic values of the elements contained in the puppet show as a puppeteer working area in performing his style. The aesthetic analytical theory which is used in this study is the concept of